Female entrepreneurship and economic crisis in EU-28: the case of Greece. (25th July 2022) - Anastasiou, Athanasios; Komninos, Dimitrios; Dermatis, Zacharias; Marinopoulou, Efcharis
Entrepreneurship is considered one of the most important solutions to unemployment, poverty and low economic growth. Creating new businesses and growing existing businesses are vital factors that contribute to any economy. Women's entrepreneurship is an important key factor in economic growth. Taking into account the period 2006-2018, we find that in Greece female entrepreneurship in its early stages is moving at slightly lower levels than in Europe and innovation countries. The high unemployment of women and the difficulties of finding dependent work seem to lead Greek women to entrepreneurship more than in European countries and innovation countries. The negative image is complemented by the fact that in Greece a woman is more likely to shut down her business compared to other European countries. The main objective of this paper is to study female entrepreneurship in the European Union crisis and the case of Greece.